Si Tou Timou Tumou Tou as a Model of Mentoring and Counseling Based on Minahasa Cultural Values: Implications for the Evangelical Church in Minahasa (GMIM) - Julio Eleazer Nendissa; Elsjani Adelin Langi2; Refail DP Sampepadang (G-Couns: Jurnal Bimbingan dan Konseling, 2026)
The philosophy of Si Tou Timou Tumou Tou has been ignored by various Minahasa communities in modern times. The essence of the philosophy is increasingly lost due to the attitude and actions of the Minahasa community, who live full of bringing each other down in order to gain self-esteem and personal dignity, attitudes that belittle others, showing off their social identity as being richer, being arrogant (not wanting more competitors), and fighting (which puts others at the lowest). The purpose of this study is to provide an understanding of Indonesian guidance and counseling for the Minahasa community or congregation, so that they maintain and convey Si Tou Timou Tumou Tou as a guideline for their daily lives that benefits others. This study uses a qualitative approach with thematic analysis of literature on Minahasa cultural values and pastoral care. The findings of this study offer a culture-based pastoral care model that can be adopted by GMIM and other religious institutions in Indonesia. Keywords: si tou timou tumou tou, indonesian assistance and counseling, GMIM